Analisis Penerimaan Pengguna Sistem Informasi Akademik STIQ Al-Lathifiyyah Menggunakan Task Technology Fit - Rifka Arlenia Putri; Reza Ade Putra; Muhammad Leandry Dalafranka (APTIKOM SUMSEL, 2022)
SIAKAD is applied to obtain all information related to computerized academic activities. One of the initial keys to the success or failure of an application/software implementation is the willingness to accept the technology among users. This study aims to measure the level of user acceptance and user ease of academic information systems and provide efficient and relevant service facilities. To obtain efficient and relevant services, it is necessary to implement a system with the best quality so that it can be accepted by users. One way that can be done is by analyzing user acceptance of academic information systems. In this study the method used is Task Technology fit (TTF). In this study, 4 variables were used, namely Task Characteristics, Technology Characteristics, Task Technology Fit, and Performance Impact. The data in this study were collected through questionnaires distributed to 135 respondents. Analysis of the data used by using the PLS-SEM tool used is SmartPLS version 3.0. The results showed that the task characteristics had no significant effect on the suitability of the task technology fit with a T-Statistics value of 0.847, the technology characteristics had a significant effect on the suitability of the task technological fit with a T-Statistics value of 13,861, and the suitability of the task technology fit had a significant effect on the performance impact with a T value. -Statistics of 5,570. From the test results, it is stated that there is 1 accepted hypothesis and 2 rejected hypotheses. The overall results of this study indicate that the acceptance of the use of SIAKAD STIQ Al-Lathifiyyah Palembang using the Task Technology Fit (TTF) Model has an effect of 97.3%. From this percentage, it can be concluded that SIAKAD STIQ Al-Lathifiyyah Palembang has been accepted and has been used by users, namely students, lecturers, and admins.